iloraz liczb -3[tex]\frac{1}{8}[/tex] i -6[tex]\frac{1}{4}[/tex] pomnóż przez -4[tex]\frac{2}{3}[/tex]

Odpowiedź :

Odpowiedź:

(-3 i 1/8) : (-6 i 1/4) = (-25/8) : (-25/4) = (-25/8) * (-4/25) = 1/2

1/2 * (-4 i 2/3) = 1/2 *(-14/3) = -7/3 = -2 i 1/3

Odpowiedź:

[tex][(-3\frac{1}{8}):(-6\frac{1}{4})]\cdot(-4\frac{2}{3})=(3\frac{1}{8}:6\frac{1}{4})\cdot(-4\frac{2}{3})=(\frac{25}{8}:\frac{25}{4})\cdot(-\frac{14}{3})=\\\\=(\frac{\not25^1}{\not8_{2}}\cdot\frac{\not4^1}{\not25_{1}})\cdot(-\frac{14}{3})=\frac{1}{\not2_{1} }\cdot(-\frac{\not14^7}{3})=-\frac{7}{3}=-2\frac{1}{3}[/tex]